Peran Kepala Sekolah dalam Meningkatkan Mutu Pendidikan - Yadi Sutikno; Hosan Hosan; Irawati Irawati (STAB Maitreyawira, 2022)
ABSTRACT Based on the observation that there are not many studies that explain the role of school principals in improving the quality of education. Whereas research on the role of school principals in improving the quality of education is important. Based on these observations, research will be conducted on the role of school principals in improving the quality of education. This research method is using a qualitative method with the type of literature study. The role of the principal in improving the quality of education is that the principal acts as an educator, the principal acts as a manager, the principal acts as an administrator, the principal acts as a supervisor, and the principal acts as an entrepreneur.